2019
DOI: 10.1111/nhs.12617
|View full text |Cite
|
Sign up to set email alerts
|

Examining unconscious bias embedded in provider language regarding children with autism

Abstract: In healthcare settings, language used by healthcare providers can influence provider-patient encounters with individuals with autism spectrum disorder, impacting feelings of stigma and marginalization. This study highlights the unconscious biases healthcare providers might have regarding their patients with autism spectrum disorder and how those beliefs are articulated. Seven pediatric dentists participated in two focus groups to describe strategies to improve oral care for children with autism spectrum disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…For example, Latinxs cite experiencing health care discrimination from providers [ 8 , 9 ] and lack of access to helpful HCPs [ 10 ]. A sense of mistrust among Latinx patients for their providers [ 11 13 ] and provider bias toward their patients [ 14 , 15 ] are also reported throughout the literature. These racial and ethnic-related barriers have the potential to influence receipt of quality health care [ 11 , 16 ] as research suggests that Latinxs receive lower quality of care compared to non-Latinx white patients, as reported by patient self-report [ 17 ] and also consensus from a panel of experts on health disparities [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Latinxs cite experiencing health care discrimination from providers [ 8 , 9 ] and lack of access to helpful HCPs [ 10 ]. A sense of mistrust among Latinx patients for their providers [ 11 13 ] and provider bias toward their patients [ 14 , 15 ] are also reported throughout the literature. These racial and ethnic-related barriers have the potential to influence receipt of quality health care [ 11 , 16 ] as research suggests that Latinxs receive lower quality of care compared to non-Latinx white patients, as reported by patient self-report [ 17 ] and also consensus from a panel of experts on health disparities [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A striking example was an older study 76 that referred to the inclusion of ‘mentally retarded’ autistic children, a term that is now startling and offensive. There is current research to evidence more subtle unconscious bias in the language used by dentists when talking about the treatment of autistic children 87 …”
Section: Discussionmentioning
confidence: 99%
“…There is current research to evidence more subtle unconscious bias in the language used by dentists when talking about the treatment of autistic children. 87 …”
Section: Discussionmentioning
confidence: 99%
“…Implicit bias, that is, unintentional prejudice and stereotyping, may have contributed to the difficulties mothers' experienced in interacting with the schools. Como, Florindez, Tran, Cermak, and Stein Duker (2019) reported that implicit biases might be held by health care providers and manifest in language when health care language includes microaggressions, marginalization, and preconceptions, highlighting biases about patients (Como et al, 2019). Professionals might unconsciously use language that could negatively impact patient-provider rapport and increase stigma the already marginalized population of mothers of children with ASD and may effect quality of care (Como et al, 2019).…”
Section: Discussionmentioning
confidence: 99%